(untitled) - Son, Hyun H. (Philippine, 2010)
This paper has two main objectives. First, it assesses and measures the gaps in the stock of human capital across the world. It presents how effectively different regions are improving their stock of human capital, and how long it will take for developing countries to catch up with the current level of human capital in industrialized countries. Second, it revisits the contribution of human capital to economic growth, proposing a decomposition method to account for employment growth—which is also impacted on by human capital growth—in explaining growth in total output per worker. The proposed methodology introduces employment growth in the growth decomposition through the employment growth elasticity. It is conjectured that as human capital increases, employment growth elasticity will decrease, making the economy less labor-intensive, resulting in higher economic growth. The proposed method points to the importance of the micro linkage between human capital and the labor market.
Keywords: Economic development,Developing countries,Phát triển kinh tế,Nước đang phát triển; Strategies,Chiến lược